A Bibliometric Analysis: Quality Standards in Vocational Education (2005-2025) - Arya Yusuf; Wagiran Wagiran; Zainal Arifin; Muhamad Riyan Maulana; Yanuar Agung Fadlullah (Journal of Educational Sciences, 2026)
This study aims to examine the development and trends in research related to quality standards in vocational education from 2005 to 2025. The research data was obtained from the Scopus database, resulting in 239 articles that met the established inclusion criteria. Bibliometric analysis was used with data extraction in CSV and RIS formats, as well as visualization using VOSviewer software. The results of the study provide an overview of the publication and citation trends over two decades regarding the most frequently cited documents, the most productive sources, leading authors, the most productive countries, and the most frequently used author keywords in this field of research. The findings show a significant increase in the number of publications, especially in the period 2015–2025, reflecting growing academic interest in this topic. Articles with the highest citation rates generally discuss the importance of clear, evidence-based quality to improving the quality standards of vocational education. In addition, the analysis shows that several countries, including United States, United Kingdom, and Netherlands play a key role in research productivity and international collaboration. Overall, this bibliometric study can serve as a reference and basis for future studies on quality standards in vocational education.